Solve the differential equation by substitution suggested by equation. Show complete solution.
(x + 2y - 1)dx + 3(x + 2y)dy = 0
Solution:
"(x + 2y - 1)dx + 3(x + 2y)dy = 0" ...(i)
Put "x+2y=v"
"\\Rightarrow dx+2dy=dv"
Using these, (i) becomes,
"(v-1)(dv-2dy)+3vdy=0\n\\\\\\Rightarrow vdv-2vdy-dv+2dy+3vdy=0\n\\\\\\Rightarrow (v-1)dv+(v+2)dy=0\n\\\\\\Rightarrow (1-v)dv=(v+2)dy\n\\\\\\Rightarrow \\dfrac{1-v}{v+2}dv=dy"
"\\\\\\Rightarrow \\dfrac{1}{v+2}dv-\\dfrac{v}{v+2}dv=dy\n\\\\\\Rightarrow \\dfrac{1}{v+2}dv-\\dfrac{v+2-2}{v+2}dv=dy\n\\\\\\Rightarrow \\dfrac{1}{v+2}dv-dv+\\dfrac{2}{v+2}dv=dy\n\\\\\\Rightarrow \\dfrac{3}{v+2}dv-dv=dy"
On integrating both sides,
"3 \\ln|v+2|-v+c=y\n\\\\\\Rightarrow 3 \\ln|x+2y+2|+x+2y+c=y\n\\\\\\Rightarrow 3 \\ln|x+2y+2|+x+y+c=0"
which is required solution.
Comments
Leave a comment